Cystatin B is essential for proliferation and interneuron migration in individuals with EPM1 epilepsy - Francesco Di Matteo; Fabrizia Pipicelli; Christina Kyrousi; Isabella Tovecci; Eduardo Penna; Marianna Crispino; Angela Chambery; Rosita Russo; Ane Cristina Ayo‐Martin; Martina Giordano; Anke Hoffmann; Emilio Ciusani; et al. (EMBO Molecular Medicine)
Abstract Progressive myoclonus epilepsy (PME) of Unverricht–Lundborg type (EPM1) is an autosomal recessive neurodegenerative disorder with the highest incidence of PME worldwide. Mutations in the gene encoding cystatin B (CSTB) are the primary genetic cause of EPM1. Here, we investigate the role of CSTB during neurogenesis in vivo in the developing mouse brain and in vitro in human cerebral organoids (hCOs) derived from EPM1 patients. We find that CSTB (but not one of its pathological variants) is secreted into the mouse cerebral spinal fluid and the conditioned media from hCOs. In embryonic mouse brain, we find that functional CSTB influences progenitors’ proliferation and modulates neuronal distribution by attracting interneurons to the site of secretion via cell‐non‐autonomous mechanisms. Similarly, in patient‐derived hCOs, low levels of functional CSTB result in an alteration of progenitor's proliferation, premature differentiation, and changes in interneurons migration. Secretion and extracellular matrix organization are the biological processes particularly affected as suggested by a proteomic analysis in patients’ hCOs. Overall, our study sheds new light on the cellular mechanisms underlying the development of EPM1.